Ceramic brick with granite texture and preparation process thereof
By spraying granite texture components on the surface of the ceramic tile body and combining them with the blank, and using supernatant as the glaze component, the existing granite texture ceramic tile has solved the problems of low three-dimensionality and complex operation, achieving high-reality texture presentation and strength improvement.
Patent Information
- Application Number
- CN202411518752.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing granite textured ceramic tiles have a low three-dimensional sense, complex operation, and traditional printing technology is difficult to achieve high-reality texture presentation.
By spraying granite texture components on the surface of the ceramic tile body and combining them with the body at high temperatures, a thin intermediate layer is formed to enhance the three-dimensional sense of the texture. At the same time, supernatant is used as one of the components of the glaze to improve the strength and texture of the ceramic tiles.
It achieves high-reality texture presentation and strength improvement of granite textured ceramic tiles, and is smooth and wear-resistant, with low water absorption.
Smart Images

Figure CN119019153B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tile production, and more particularly to a ceramic tile with granite texture and a preparation process thereof. Background Art
[0002] Granite textured ceramic tiles, i.e. imitation granite tiles, use advanced inkjet printing technology to accurately print the designed granite texture pattern on the surface of the ceramic tile blank. This technology can achieve high-resolution texture presentation, making the texture pattern more realistic and delicate.
[0003] However, with regard to the existing technology, the granite pattern is random and has a three-dimensional effect, and the manufactured granite texture ceramic tiles only have textures, a low three-dimensional effect, and are complicated to operate. Therefore, the present invention provides a ceramic tile with a granite texture and a preparation process thereof. Summary of the invention
[0004] In order to overcome the above defects of the prior art, the present invention provides a ceramic tile with a granite texture and a preparation process thereof to solve the problems existing in the above background technology.
[0005] The present invention provides the following technical solution: a ceramic tile with a granite texture, comprising the following components:
[0006] Ceramic tile ingredients: 10-20 parts of clay; 5-10 parts of feldspar, 1-5 parts of stabilizer; 1-5 parts of flux, 2-6 parts of quartz particles;
[0007] Texture composition: 10-20 parts of feldspar, 5-10 parts of quartz particles, 1-5 parts of mica;
[0008] Glaze ingredients: 5-10 parts of potassium feldspar, 5-10 parts of sodium feldspar, 10-20 parts of quartz particles; 1-5 parts of metal oxides, 0-1% of colorant iron oxide; glaze is an extremely thin layer of substance covering the surface of the body, which can protect and decorate the body.
[0009] In terms of composition, the composition of glaze is similar to that of body. The main components are feldspar, quartz and kaolin, but the proportions are different. The flux components (such as feldspar) in glaze are more than those in body. During the firing process, the glaze can melt and then cover the surface of body. Due to the difference in composition, body and glaze will diffuse towards each other at high temperature, and a thin intermediate layer will develop between body and glaze, making the body and glaze firmly combined.
[0010] The viscous material is squeezed and pulled up, and then after drying, the raised parts of the surface are removed, so that the concave parts in the un-squeezed layer form an uneven and rough granite, thereby improving the three-dimensional sense of the granite texture;
[0011] A process for preparing a ceramic tile with a granite texture comprises the following steps:
[0012] S1. Raw material pretreatment: feldspar, stabilizer, flux and quartz are mixed and ground in a ball mill to obtain a mixture powder. The mixture powder is added with an appropriate amount of water and clay and stirred to form a slurry. The iron removal operation is performed. During the iron removal operation, the magnetic material in the slurry is removed by using a magnetic separator, and the next operation is performed after the selection.
[0013] S2, slurry precipitation and drying; after the slurry after iron removal is allowed to stand, the supernatant is collected, and then the remaining precipitated slurry is stirred until the stirring is completed to form a slurry with a higher concentration, and part of the slurry is taken out for standby use. At this time, the remaining slurry is dried and poured into a spray tower through a pipeline for drying, thereby obtaining a dried granular powder;
[0014] S3, rough blank production: by feeding the granular powder into the press to press out the ceramic tile rough blank, at the same time, by placing a mold with imitation granite texture on the top of the granular material when the press is pressing, it is ensured that when the press is pressing, a depression with granite texture will be formed on the surface of the rough blank, and it is transferred to the drying and shaping step:
[0015] S4, drying and shaping: the rough blank is conveyed to the air-drying kiln through the conveyor belt, and air-dried in the air-drying kiln. After air-drying, the granite grain mold is taken out, and the next step is performed after taking out, spraying the granite grain filler, by spraying the granite grain components on the dry rough blank granite depressions, after spraying, ensure that the particles are evenly distributed and there is no problem of excessive accumulation. After confirming that the granite depressions are sprayed, vibration operation is required to ensure that the grain components can be evenly distributed in the air-dried and shaped rough blank mold;
[0016] S5. Mud spraying: After spraying granite texture particles in the granite depression, add the backup mud to pour a small amount of mud liquid into the rough granite sprayed with it, ensuring that the slurry does not immerse more than one-third of the texture component;
[0017] S6. Slight compaction: After the slurry is sprayed and left to stand for 15-30 minutes, secondary compaction is performed. During the secondary compaction, all the texture components are pressed flush. After pressing flush, secondary air drying is performed to obtain a rough granite texture blank:
[0018] S7, glazing operation: spraying glaze on the granite texture rough blank after secondary air drying, wherein the glaze is mixed by using the supernatant as the mixed liquid to obtain glaze water; and spraying glaze with the glaze water;
[0019] S8, calcination treatment: conveying to a calcination kiln via a conveyor belt for calcination;
[0020] S9, cooling and packaging: After calcination, the products are transported by conveyor belt and inspected on the conveyor belt for quality. If they are qualified, they will be packaged after cooling, and if they are unqualified, they will be discarded.
[0021] Furthermore, the flux components in the ceramic tile composition are sodium oxide and potassium oxide, and the stabilizer components are aluminum oxide and calcium oxide.
[0022] Furthermore, the metal oxides in the glaze composition include potassium oxide, sodium oxide, zinc oxide, boron oxide, calcium oxide and aluminum oxide.
[0023] Furthermore, the slurry spraying in S5 is performed by adding 0.1-1 parts of ball-milled iron oxide to the spare slurry and stirring the mixture before spraying.
[0024] Technical effects and advantages of the present invention:
[0025] The present invention adopts the supernatant liquid left to stand after stirring the blank as one of the raw materials of the glaze, collects the supernatant liquid, firstly increases the wetness to facilitate iron removal, and adds the supernatant liquid after standing to the glaze to further improve the strength of the ceramic tile with granite texture. At the same time, the granite texture is artificially manufactured and pressed, so that the manufactured ceramic tile is displayed in an interlayer manner, has the texture of granite and the reflective property of ceramic tile, is smooth and wear-resistant, and has a three-dimensional sense compared with the traditional method of spraying the granite texture on the surface of the ceramic tile by printing, making the granite texture extremely real. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a texture similarity line graph showing the effect of the iron oxide content in the blank of the present invention on the granite texture of the ceramic tile.
[0027] Figure 2 It is a line graph showing the effect of the iron oxide content in the blank of the present invention on the compressive strength of the granite texture of the ceramic tile.
[0028] Figure 3 It is a line graph showing the effect of the iron oxide content in the blank of the present invention on the flexural resistance of the granite texture of the ceramic tile.
[0029] Figure 4It is a texture similarity line graph showing the effect of the feldspar content in the glaze of the present invention on the granite texture of the ceramic tile.
[0030] Figure 5 It is a line graph showing the effect of the feldspar content in the glaze of the present invention on the compressive strength of the granite texture of the ceramic tile.
[0031] Figure 6 It is a line graph showing the effect of the feldspar content in the glaze of the present invention on the flexural resistance of the granite texture of the ceramic tile.
[0032] Figure 7 It is a texture similarity line graph showing the effect of the quartz content in the glaze of the present invention on the granite texture of the ceramic tile.
[0033] Figure 8 It is a line graph showing the effect of the quartz content in the glaze of the present invention on the compressive strength of the granite texture of the ceramic tile.
[0034] Fig. 9 It is a line graph showing the effect of the quartz content in the glaze of the present invention on the flexural resistance of the granite texture of the ceramic tile.
[0035] Fig.10 It is a line graph showing the water absorption rate of the granite texture of the ceramic tile affected by the quartz content in the glaze of the present invention.
[0036] Fig.11 It is a texture similarity line graph showing the influence of the metal oxide and supernatant content in the glaze of the present invention on the granite texture of the ceramic tile.
[0037] Fig.12 It is a line graph showing the influence of the metal oxide and supernatant content in the glaze of the present invention on the compressive strength of the granite texture of the ceramic tile.
[0038] Fig.13 The figure is a line graph showing the influence of the metal oxide and supernatant content in the glaze of the present invention on the flexural resistance of the granite texture of the ceramic tile.
[0039] Fig.14 It is a line graph showing the water absorption rate of the granite texture of ceramic tiles, which shows the influence of the metal oxide and supernatant content in the glaze of the present invention.
[0040] Fig.15 This is a diagram showing a ceramic tile with a granite texture according to the present invention. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the present invention. In addition, the forms of the various structures recorded in the following embodiments are merely illustrative. The ceramic tiles with granite texture and the preparation process thereof involved in the present invention are not limited to the various structures recorded in the following embodiments. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] Reference Figure 1 and Figure 2 The present invention provides a ceramic tile with granite texture and a preparation process thereof, comprising the following components:
[0043] Ceramic tile ingredients: 10-20 parts of clay; 5-10 parts of feldspar, 1-5 parts of stabilizer; 1-5 parts of flux, 2-6 parts of quartz particles;
[0044] Texture composition: 10-20 parts of feldspar, 5-10 parts of quartz particles, 1-5 parts of mica;
[0045] Glaze ingredients: 5-10 parts of potassium feldspar, 5-10 parts of sodium feldspar, 10-20 parts of quartz particles; 1-5 parts of metal oxides, 0-1% of colorant iron oxide; glaze is an extremely thin layer of substance covering the surface of the body, which can protect and decorate the body.
[0046] In terms of composition, the composition of glaze is similar to that of body. The main components are feldspar, quartz and kaolin, but the proportions are different. The flux components (such as feldspar) in glaze are more than those in body. During the firing process, the glaze can melt and then cover the surface of body. Due to the difference in composition, body and glaze will diffuse into each other at high temperature, and a thin intermediate layer will develop between body and glaze, making the body and glaze firmly bonded.
[0047] The viscous material is squeezed and pulled up, and then dried, and the raised parts of the surface are removed, leaving the recessed layers that have not been squeezed to form an uneven and rough granite surface, thereby enhancing the three-dimensional effect of the granite texture.
[0048] A process for preparing a ceramic tile with a granite texture comprises the following steps:
[0049] S1. Raw material pretreatment: feldspar, stabilizer, flux and quartz are mixed and ground in a ball mill to obtain a mixture powder. The mixture powder is added with an appropriate amount of water and clay and stirred to form a slurry. The iron removal operation is performed. During the iron removal operation, the magnetic material in the slurry is removed by using a magnetic separator, and the next operation is performed after the selection.
[0050] S2, slurry precipitation and drying; after the slurry after iron removal is allowed to stand, the supernatant is collected, and then the remaining precipitated slurry is stirred until the stirring is completed to form a slurry with a higher concentration, and part of the slurry is taken out for standby use. At this time, the remaining slurry is dried and poured into a spray tower through a pipeline for drying, thereby obtaining a dried granular powder;
[0051] S3, rough blank production: by feeding the granular powder into the press to press out the ceramic tile rough blank, at the same time, by placing a mold with imitation granite texture on the top of the granular material when the press is pressing, it is ensured that when the press is pressing, a depression with granite texture will be formed on the surface of the rough blank, and it is transferred to the drying and shaping step:
[0052] S4, drying and shaping: the rough blank is conveyed to the air-drying kiln through the conveyor belt, and air-dried in the air-drying kiln. After air-drying, the granite grain mold is taken out, and the next step is performed after taking out, spraying the granite grain filler, by spraying the granite grain components on the dry rough blank granite depressions, after spraying, ensure that the particles are evenly distributed and there is no problem of excessive accumulation. After confirming that the granite depressions are sprayed, vibration operation is required to ensure that the grain components can be evenly distributed in the air-dried and shaped rough blank mold;
[0053] S5. Mud spraying: After spraying granite texture particles in the granite depression, add the backup mud to pour a small amount of mud liquid into the rough granite sprayed with it, ensuring that the slurry does not immerse more than one-third of the texture component;
[0054] S6. Slight compaction: After the slurry is sprayed and left to stand for 15-30 minutes, secondary compaction is performed. During the secondary compaction, all the texture components are pressed flush. After pressing flush, secondary air drying is performed to obtain a rough granite texture blank:
[0055] S7, glazing operation: spraying glaze on the granite texture rough blank after secondary air drying, wherein the glaze is mixed by using the supernatant as the mixed liquid to obtain glaze water; and spraying glaze with the glaze water;
[0056] S8, calcination treatment: conveying to a calcination kiln via a conveyor belt for calcination;
[0057] S9, cooling and packaging: After calcination, the products are transported by conveyor belt and inspected on the conveyor belt for quality. If they are qualified, they will be packaged after cooling, and if they are unqualified, they will be discarded.
[0058] Furthermore, the flux components in the ceramic tile composition are sodium oxide and potassium oxide, and the stabilizer components are aluminum oxide and calcium oxide.
[0059] Furthermore, the metal oxides in the glaze composition include potassium oxide, sodium oxide, zinc oxide, boron oxide, calcium oxide and aluminum oxide.
[0060] Furthermore, the slurry spraying in S5 is performed by adding 0.1-1 parts of ball-milled iron oxide to the spare slurry and stirring the mixture before spraying.
[0061] Prepared according to the production process:
[0062] Texture composition: 10-20 parts of feldspar, 5-10 parts of quartz particles, 1-5 parts of mica;
[0063] Mud spraying: After spraying the granite texture particles in the granite depression, add the backup mud and then pour a small amount of mud into the rough granite sprayed with it, making sure that the slurry does not submerge more than one-third of the texture component:
[0064] Slight compaction: After the mud is sprayed and left to stand for 15-30 minutes, secondary compaction is carried out. During the secondary compaction, all the texture components are pressed flush. After pressing flush, secondary air drying is carried out to obtain a rough granite texture blank;
[0065] The slurry spraying in S5 is performed by adding 0.1-1 parts of ball-milled iron oxide to the spare slurry and stirring the mixture before spraying;
[0066] By setting up multiple groups of control cases for comparison:
[0067] Control group 1, the reserve mud had an iron oxide content of 0.1 part and was left to stand for 15 minutes;
[0068] Control group 2, the reserve mud had an iron oxide content of 0.2 parts and was left to stand for 15 minutes;
[0069] Control group 3, the reserve mud had an iron oxide content of 0.3 parts and was left to stand for 15 minutes;
[0070] Control group 4, the reserve mud had an iron oxide content of 0.4 parts and was left to stand for 15 minutes;
[0071] Control group 5, the reserve mud has an iron oxide content of 0.5 parts and is allowed to stand for 15 minutes.
[0072] Control group 6, the reserve mud had an iron oxide content of 0.6 parts and was left to stand for 15 minutes;
[0073] Control group 7, the reserve mud had an iron oxide content of 0.7 parts and was left to stand for 15 minutes;
[0074] Control group 8, the reserve mud had an iron oxide content of 0.8 parts and was left to stand for 15 minutes;
[0075] Control group 9, the reserve mud had an iron oxide content of 0.9 parts and was left to stand for 15 minutes;
[0076] Control group 10, spare mud iron oxide content 1 part, let stand for 15 minutes.
[0077] The same slurry spraying and resting time were set to determine the effect of different iron oxide contents in the slurry on the granite texture of ceramic tiles;
[0078] Through the above experiments, it can be concluded that under the traditional glazing method, when using 0.3 iron oxide as one of the spare mud raw materials for spraying, the texture components on the rough surface can be more closely matched with the granite texture. When laminating, in the test of compression, flexural and wear resistance, 20 cm x 20 cm (0.04 m²) tiles were used for experiments. It can be known that in the case of 0.3 iron oxide, a higher use strength can be achieved, and the compression resistance is about 1690N, and the flexural resistance is about 1390N, which is converted into a compressive strength of 42.5MPa, a flexural strength of 34MPa, and a wear resistance of level 5. At the same time, the water absorption rate also meets the standard and has low water absorption. At the same time, by using a slight compaction technology, after compacting it, the texture components are pressed to the same level to ensure that the texture is below the glaze layer and is flush when calcined after glazing, and the flatness of the granite texture is ensured at this time.
[0079] In order to improve the strength of the ceramics with granite texture produced by this method, the following operations were also carried out:
[0080] Glazing operation: spraying glaze on the rough granite texture after secondary air drying, wherein the glaze is mixed by using the supernatant as the mixed liquid to obtain glaze water; spraying glaze with the glaze water;
[0081] Glaze ingredients: 5-10 parts of potassium feldspar, 5-10 parts of sodium feldspar, 10-20 parts of quartz particles; 1-5 parts of metal oxides, 0-1% of iron oxide as colorant;
[0082] By setting up multiple control groups for comparison:
[0083] The experimental group used conventional glaze;
[0084] Control group 1, potassium feldspar 5 parts, sodium feldspar 5 parts, quartz particles 10 parts; metal oxide 1 part, iron oxide 0%;
[0085] Control group 2, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 10 parts; metal oxide 1 part, iron oxide 0%;
[0086] Control group 3, potassium feldspar 10 parts, sodium feldspar 10 parts, quartz particles 10 parts; metal oxide 1 part, iron oxide 0%;
[0087] Effect Experiment Control group 1 Control group 2 Control group 3 Experimental Group Texture Similarity 80% 86% 84% 80% Stress resistance 1550 1580 1670 1690 Bending resistance 1340 1360 1375 1390 Wear-resistant 5 5 5 5 Water absorption 0.75% 0.76% 0.72% 1%
[0088] The same quartz particles, metal oxides, and iron oxide content were set to determine the effect of granite texture on ceramic tiles;
[0089] Through the above experiments, it can be concluded that under the traditional glazing method, the compressive and flexural resistance are better than tiles with the same quartz particles, metal oxides, and iron oxide content, but it does not have advantages in the similarity of granite texture and water absorption. Because potassium feldspar is added because potassium feldspar is rich in potassium and aluminum, the sintering temperature is reduced, making it less likely to have pores, thereby reducing the water absorption rate, and sodium feldspar can enhance the texture of the glaze, making it more uniform, and smoother after sintering, and better reflecting the granite texture;
[0090] Control group 4, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 10 parts; metal oxide 1 part, iron oxide 0%;
[0091] Control group 5, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 12.5 parts; metal oxide 1 part, iron oxide 0%.
[0092] Control group 6, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 15 parts; metal oxide 1 part, iron oxide 0%.
[0093] Control group 7, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 17.5 parts; metal oxide 1 part, iron oxide 0%.
[0094] Control group 8, potassium feldspar 7.5 parts, sodium feldspar 7.5 parts, quartz particles 20 parts; metal oxide 1 part, iron oxide 0%.
[0095] The specific contents of the form are as follows:
[0096] Effect Experiment Control group 4 Control group 5 Control group 6 Control group 7 Control group 8 Experimental Group Texture Similarity 83% 84% 86% 90% 89% 80% Stress resistance 1700 1720 1730 1750 1740 1690 Bending resistance 1420 1440 1450 1460 1430 1390 Wear-resistant 5 5 5 5 5 5 Water absorption 0.5% 0.5% 0.45% 0.43% 0.43% 1%
[0097] Through experiments, we know that when 7.5 parts of potassium feldspar, 7.5 parts of sodium feldspar and 17.5 parts of quartz particles are used, the granite texture ceramic tile has the highest strength, and both the similarity and water absorption are the best. However, in fact, the SSIM algorithm used in the similarity graph is used for percentage measurement. The algorithm is calculated after storing common granite data in the database.
[0098] In order to further improve the strength of the granite texture, the slurry after iron removal is allowed to stand, and the supernatant is collected and added as one of the components of the glaze. By utilizing the feldspar particles, quartz particles, clay particles, and some metal oxides contained in the supernatant, the addition of the supernatant can reduce the amount of metal oxides needed to be added to the glaze. By using the same raw materials as the rough blank, the glaze layer can better penetrate into the gaps of the texture components during glazing to eliminate the problem of voids. Because the supernatant is made of the same material as the blank, the glaze has a higher mutual penetration with the rough blank and the secondary air-dried blank, further reducing the existence of voids. Through experiments, we can know that:
[0099] The amount of supernatant added was controlled to control the addition of metal oxides, and the following experiments were performed:
[0100] Experimental group 1: No supernatant was added, but 1 part of metal oxide was added;
[0101] Experimental group 2: No supernatant was added, but 2 parts of metal oxide were added;
[0102] Experimental group 3: No supernatant was added, but 3 parts of metal oxide were added;
[0103] Experimental group 4: No supernatant was added, but 4 parts of metal oxide were added;
[0104] Experimental group 5: no supernatant was added, but 5 parts of metal oxide were added;
[0105] Control group 1: 1 part of supernatant and 1 part of metal oxide were added;
[0106] Control group 2: 2 parts of supernatant and 1 part of metal oxide were added;
[0107] Control group 3: 3 parts of supernatant and 1 part of metal oxide were added;
[0108] Control group 4: 4 parts of supernatant and 1 part of metal oxide were added;
[0109] Control group 5: 5 parts of supernatant and 1 part of metal oxide were added;
[0110] In summary, it can be concluded that the use of supernatant as a substitute for metal oxides in glaze can provide higher strength to granite texture tiles, while also reducing water absorption. Therefore, the use of supernatant can improve the strength of the glaze, further improve the similarity to the granite texture, and at the same time reduce water absorption.
[0111] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing a ceramic tile with a granite texture, characterized in that: The following steps are involved: S1. Raw material pretreatment: feldspar, stabilizer, flux and quartz are mixed and ground using a ball mill. After grinding, a mixture powder is obtained. A proper amount of water is added to the mixture powder, and clay is added together and stirred. After stirring, a slurry is formed. At this time, an iron removal operation is performed. During the iron removal operation, the magnetic material in the slurry is removed by using a magnetic separator, and the next operation is performed after the removal; S2, slurry precipitation and drying; after the slurry after iron removal is allowed to stand, the supernatant is collected, and the remaining precipitated slurry is stirred until the stirring is completed to form a high-concentration slurry, and part of the slurry is taken out for standby use. At this time, the remaining slurry is dried and poured into a spray tower through a pipeline for drying, thereby obtaining a dried granular powder; S3, rough blank production: the granular powder is fed into the press to press out the ceramic tile rough blank. When the press is pressing, a mold with imitation granite texture is placed on the top of the granular powder to ensure that when the press is pressing, a depression with granite texture will be formed on the surface of the rough blank, and it is transferred to the drying and shaping step: S4, drying and shaping: the rough blank is conveyed to the air-drying kiln through the conveyor belt, and air-dried in the air-drying kiln. After air-drying, the granite texture mold is taken out, and the next step is performed after taking out, spraying the granite texture filler, spraying the texture components of the granite on the concave parts of the dry rough blank granite. After spraying, ensure that the particles are evenly distributed and there is no problem of excessive accumulation. After confirming that the spraying of the granite concave parts is completed, it is necessary to perform a vibration operation to ensure that the texture components can be evenly distributed in the air-dried and shaped rough blank; S5. Mud spraying: After spraying the granite texture particles in the granite depression, pour a small amount of backup mud liquid into the rough blank to ensure that the slurry does not immerse more than one-third of the texture component; S6. Slight compaction: After the slurry is sprayed and left to stand for 15-30 minutes, secondary compaction is performed. During the secondary compaction, all texture components are pressed flush. After pressing flush, secondary air drying is performed to obtain a rough granite texture blank: S7, glazing operation: spraying glaze on the granite texture rough blank after secondary air drying with glaze water, wherein when the glaze is mixed, the supernatant is used as the mixed liquid to obtain the glaze water; S8, calcination treatment: conveying to a calcination kiln via a conveyor belt for calcination; S9, cooling and packaging: after calcination, the products are transported by conveyor belt and inspected on the conveyor belt to see if they are qualified. If they are qualified, they are packaged after cooling, and if they are unqualified, they are discarded; The granite texture ceramic tiles include the following components: Ceramic tile ingredients: 10-20 parts of clay; 5-10 parts of feldspar, 1-5 parts of stabilizer; 1-5 parts of flux, 2-6 parts of quartz particles; Texture composition: 10-20 parts of feldspar, 5-10 parts of quartz particles, 1-5 parts of mica; Glaze ingredients: 5-10 parts of potassium feldspar, 5-10 parts of sodium feldspar, 10-20 parts of quartz particles; 1-5 parts of metal oxides; The flux components in the ceramic brick composition are sodium oxide and potassium oxide, and the stabilizer components are aluminum oxide and calcium oxide.
2. The process for preparing a ceramic tile with a granite texture according to claim 1, characterized in that: The metal oxides in the glaze composition include potassium oxide, sodium oxide, zinc oxide, boron oxide, calcium oxide and aluminum oxide.
3. The process for preparing a ceramic tile with a granite texture according to claim 1, characterized in that: When spraying the slurry of S5, 0.1-1 part of ball-milled iron oxide is added and stirred with the reserved slurry before spraying.
4. A ceramic tile prepared using the preparation process described in any one of claims 1 to 3.
Citation Information
Patent Citations
Ceramic rock plate imitating terrazzo surface texture and preparation method thereof
CN115872782A